2016
DOI: 10.3390/brainsci6040042
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Donor and Recipient Nerves Utilised in Nerve Transfers to Restore Upper Limb Function in Cervical Spinal Cord Injury

Abstract: Loss of hand function after cervical spinal cord injury (SCI) impacts heavily on independence. Multiple nerve transfer surgery has been applied successfully after cervical SCI to restore critical arm and hand functions, and the outcome depends on nerve integrity. Nerve integrity is assessed indirectly using muscle strength testing and intramuscular electromyography, but these measures cannot show the manifestation that SCI has on the peripheral nerves. We directly assessed the morphology of nerves biopsied at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…After SCI, peripheral nerves carrying motor, sensory, and autonomic axons have severe morphological disorders [61,62]. In our study, morphometric analysis of the tibial fascicle of the sciatic nerve in control mini pigs revealed a decrease in the number of myelinated fibers and an increase in myelin thickness and nerve fiber axon diameter.…”
Section: Peripheral Nervesmentioning
confidence: 44%
“…After SCI, peripheral nerves carrying motor, sensory, and autonomic axons have severe morphological disorders [61,62]. In our study, morphometric analysis of the tibial fascicle of the sciatic nerve in control mini pigs revealed a decrease in the number of myelinated fibers and an increase in myelin thickness and nerve fiber axon diameter.…”
Section: Peripheral Nervesmentioning
confidence: 44%
“…However, the axonal dysfunction could result from local, rather than systemic processes. The inflammatory response noted by Messina et al [36] was based on the observation of epineural vessel and connective tissue localisation of mononuclear blood cells, neutrophils, lymphocytes (Figure 1D) and mast cells (Figure 1E). Inflammation of the peripheral nervous system in patients with SCI may either contribute to, or be a response to, the abnormalities observed.…”
Section: Inflammationmentioning
confidence: 83%
“…Fox et al [32] described decreased fibre density in two of seven anterior interosseous nerves sampled at the time of nerve transfer surgery. In our recent, more extensive morphological study [36] specimens of donor and recipient nerves were collected from three participants with cervical SCI who were referred for surgical reanimation of hand function. Donor nerves included teres minor, posterior axillary, brachialis, extensor carpi radialis brevis and supinator.…”
Section: Histological Abnormalities In Human Peripheral Nervesmentioning
confidence: 99%
“…Two studies provided histological estimates of axon number in putative recipients, and Jain linked these to the presence of a CMAP in APB on motor NCS 36,50 . Fox et al wrote a qualitative study about the experience of patients with SCI undergoing assessment, surgery, and rehabilitation of nerve transfers 51 .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies provided histological estimates of axon number in putative recipients, and Jain linked these to the presence of a CMAP in APB on motor NCS. 36,50 Fox et al wrote a qualitative study about the experience of patients with SCI undergoing assessment, surgery, and rehabilitation of nerve transfers. 51 Pertaining to the clinical electrophysiological evaluation, a patient suggested that the EDX provider should have an appreciation of the patient experience in addition to the purpose of the test, its role in the PNT surgery, and be able to explain this to the patient, taking into account how results may affect surgical decision-making.…”
Section: Studies Addressing Other Principles In Edxmentioning
confidence: 99%